The effect of mobile phone addiction on perceived stress and mediating role of ruminations: Evidence from Chinese and Czech university students - Liu, Hongyang; Novotný, Jan Sebastian; Váchová, Lucie (Frontiers in Psychology, 2022)
The rise in the capabilities of mobile devices and the associated increase in the proportion of time we spend on them has not only positive benefits but also several risks, including mobile phone addiction and its consequences. The complex mechanisms of the impact of this addiction on mental health, especially in a cross-cultural context, however, remain relatively unknown. The aim of this cross-cultural study was to investigate the mediating role of rumination on the association between mobile phone addiction and perceived stress. A population of 358 Chinese and 282 Czech university students was tested using a battery of validated psychological tests that included a short version of the Smartphone Addiction Scale (SAS-SV), the Ruminative Response Scale (RRS), and the Perceived Stress Scale (PSS). The results showed significant cross-cultural differences with Czech students manifesting greater rumination (d=0.79) and perceived stress (d=0.42) and Chinese students showing greater mobile phone addiction (d=1.01). Mediation analyses showed that the effect of mobile phone addiction on stress levels was mediated through the rumination in both populations (45.6 and 80.9% of the explained variance for Chinese and Czech students, respectively) and did not differ between the two countries (estimate of difference [95%CI]=-0.052[-0.166, 0.037], P=0.27). In contrast, the significant direct effect of mobile phone addiction on perceived stress was only present in Chinese students, where it was marginally larger than the indirect effect. In Czech students, the direct effect was not manifested and the difference between countries was significant (estimate of difference [95%CI]=0.242 [0.035, 0.413], P<0.001). In all of the cases, the association between the variables was positive, i.e., as one grew, so did the other. Finally, a moderated-mediation analysis confirmed that country of origin significantly moderated only the direct relationship between mobile phone dependence and perceived stress (P=0.002). These results suggest that the mechanism of interaction between excessive mobile phone use and perceived stress is culturally conditioned, which may limit the transferability of research findings in a global context and requires further cross-cultural studies.